Pendampingan Usaha Produk Stick Ubi Jalar Balado - Melo, Ramla Hartini; Niode, Syarifah Fatimah Setiasih; Dunggio, Iswan; Blongkod, Agnes; Mohamad, Aina; Diman, Ruswinda S.; Alamri, Istiqomah (-, 2025)
This mentoring activity focuses on the development and production of three innovative food products made from mangrove flour, namely mangrove lumpia sticks, mangrove chips, and mangrove balls. Although the title of the program still refers to the previous activity, “Pendampingan Usaha Produk Stick Ubi Jalar Balado”, the implementation has been directed toward utilizing alternative raw materials that are more environmentally friendly and have high economic potential. The mentoring process was carried out through material delivery, hands-on production practice, and guidance in preparing business plans and marketing strategies. The activity resulted in increased student creativity and introduced the use of mangrove flour as a valuable local food resource with economic prospects.